Territorial Development in Argentina : Diagnosing Key Bottlenecks as the First Step Toward Effective Policy - World Bank (World Bank, Washington, DC, 2020)
Argentina’s population and economic activity is highly concentrated in few places, similar to global trends. But unlike countries like South Korea, the concentration of economic activity has not been balanced by successful efforts to improve living standards across the country. How can the government reduce development gaps across the national territory while at the same time supporting growth opportunities within a context of national fiscal deficit? Using a territorial development lens that allows the identification of challenges and opportunities at the sub-national level, this report provides a framework and diagnostics to understand Argentina through three dimensions of scale, specialization, and convergence. Chapter 1 explains the territorial development framework used for the analysis. Chapter 2 provides an overview of the economic geography of Argentina and the challenges the country faces along these three dimensions. Chapter 3 presents a closer look at two provinces, Salta and Jujuy, and puts them under the same lens. Chapter 4 summarizes the key messages of the report, providing benchmarking to compare Argentina to other countries around the world in scale, specialization, and convergence.